Problematika Pembelajaran Matematika Berbasis Kurikulum 2013 (Studi Kasus Kelas VII Di SMP Negeri 4 Klaten) - Pratama, Muhammad Alif; , Dra. Sri Sutarni, M.Pd; , Muhammad Noor Kholid, S.Pd., M.Pd (2016)
This study aimed to describe what the problems faced by teachers prior to the learning process, the learning process after the learning process of mathematics curriculum 2013 based SMP Negeri 4 Klaten. This research is a qualitative research case study. The subjects were two teachers who teach mathematics in class VII SMP N 4 Klaten, selected by purposive sampling. Data collection techniques in this research is participant observation, semi-structured interviews and document study. Data analysis was performed periodically during and after the collection of data through three stages, namely: (1) data reduction, (2) presentation of data, and (3) conclusion and verification. Mechanical data validity checking is done by triangulation techniques and triangulation of sources. The results were obtained in the planning of teacher learning proses` sometimes do not make the lesson plan before teaching process. RPP found in the material component not explained by category, facts, concepts, principles and procedures. RPP components made yet refers to the attachment Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 103 of 2014 on Learning In Primary and Secondary Education. On the implementation of the learning problems of the teachers do not convey the indicators and the learning objectives in the preliminary activities. Props and learning media in scool not optimal. In the scientific approach to question aspects and aspects of communicating less than the maximum. The findings of the study indicate that there are problems and constraints faced by teachers in the process of learning assessment models based mathematics curriculum, 2013. Teacher did appraisal observation, self-assessment, assessment journals, oral assessment, and assessment of the portfolio periodically. In the implementation of remediation teacher do constraint of time in the implementation of remedial actions.